Managing retirement incomes - James Banks; Rowena Crawford (Institute for Fiscal Studies (IFS), 2022)
In this paper we discuss the state of the literature relating to the decumulation of retirement wealth and the management of retirement incomes. On the one hand, life-cycle models which allow for strong bequest motives and the effects of medical expense risks have been shown to be able to rationalise retirees' wealth, income and consumption trajectories. On the other, studies of individual asset choices and portfolio decisions seem to suggest low levels of financial literacy and engagement, and non-negligible consequences of age-related cognitive decline on financial decision making. We argue that future work should try to reconcile these two sets of conflicting findings into a coherent and holistic evidence base to inform policy, since issues around the management of retirement incomes, and insurance against different risks in retirement more generally, will become increasingly important for future cohorts of retirees.
Keywords: 330; Rentner; Haushaltseinkommen; Vermögen; Private Finanzplanung; Finanzwissen